2005
DOI: 10.5326/0410012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Boric-Complexed Zinc and Acetic-Complexed Zinc Otic Preparations for Canine Yeast Otitis Externa

Abstract: The purpose of this 2-week, double-blinded, controlled clinical trial was to evaluate the efficacy of topical amino acid-complexed zinc gluconate formulated with boric acid (ZGB) or acetic acid (ZGA) versus a topical placebo in the treatment of yeast otitis externa in dogs. Included in the study were dogs with otitis externa and a cytopathological finding of yeast organisms in the affected ear. Ears were treated with the placebo, ZGA, or ZGB medications. Yeast counts as well as clinical appearance of the ears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Boric acid is commonly used as a treatment for human fungal otitis . In one in vivo study, a boric acid‐complexed zinc gluconate cleaner was found to be efficacious, in contrast to an acetic acid‐complexed zinc gluconate cleaner . The in vivo antiyeast activity of MalAcetic Aural ® has been reported previously .…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Boric acid is commonly used as a treatment for human fungal otitis . In one in vivo study, a boric acid‐complexed zinc gluconate cleaner was found to be efficacious, in contrast to an acetic acid‐complexed zinc gluconate cleaner . The in vivo antiyeast activity of MalAcetic Aural ® has been reported previously .…”
Section: Discussionmentioning
confidence: 70%
“…21 In one in vivo study, a boric acid-complexed zinc gluconate cleaner was found to be efficacious, in contrast to an acetic acid-complexed zinc gluconate cleaner. 18 The in vivo antiyeast activity of Mal-Acetic Aural â has been reported previously. 22 In view of other study results, it seems likely that it is the 2% boric acid in this product that confers its anti-Malassezia activity.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations